Molecular Profiling of Dillenia suffruticosa in Bangka Islands using rbcL Gene - Arsyadi, Ahmad; Saputri, Rinny (Program Study of Biology, Science and Technology Faculty, UIN Maulana Malik Ibrahim Malang, 2025)
Dillenia suffruticosa or Simpur is known for their multiple uses in various medical and food packaging purposes. Considering their applications and valuable potential, implementing conservation strategies is required to ensure their survival and preserve their genetic diversity. In this study, we complemented the traditional methods with DNA barcoding for identifying plant species. The current study was designed to accurately identify D. suffruticosa collected from Bangka Islands in Indonesia, through the molecular analysis using rbcL gene as marker genetic. The DNA barcode was examined using several approaches including plant sample collection, DNA extraction, PCR amplification, and DNA sequencing. The obtained DNA sequences were analyzed using various bioinformatics tools to assess genetic relationships and confirm species identification. Based on our analysis, the specimen was successfully identified by DNA barcoding. An approximately 606 base-pair sequence of the rbcL gene from was amplified from D. suffruticosa, which showed 99% similarity to a species from Hawaii. Furthermore, phylogenetic analysis demonstrated that the rbcL barcode loci used was effective in assigning samples accurately at the genus level, but rather challenging in resolving taxa at the species level. Our findings highlight the potential of DNA barcoding as a powerful tool for identifying members of Dilleniaceae, offering advantages over conventional identification methods. This study also was the first to identify the D. suffruticosa in Bangka Islands with the help of DNA barcoding method. However, future research should include additional genetic markers to establish a more robust and accurate method for species identification.